Orthogonal Phase Demodulation of Optical Fiber Fabry-Perot Interferometer Based on Birefringent Crystals and Polarization Technology - Yi Huang; Shuang Wang; Junfeng Jiang; Kun Liu; Xuezhi Zhang; Peng Zhang; Tiegen Liu (IEEE Photonics Journal, 2020)
In this paper, we propose and demonstrate the optical fiber Fabry-Perot (F-P) interferometer based on birefringent crystals and polarization technology. For recovering the variation signals, the orthogonal signals are obtained based on the birefringent crystal characteristics and the proposal thickness difference between the two crystals. The differential cross multiplication (DCM) algorithm is utilized to demodulate the orthogonal signals to obtain the phase variation of the optical fiber F-P sensor. The proposed interferometer has a minimum detection phase of 0.014 $\text{rad}/\sqrt {\text{Hz}} $ at the frequency of 25 kHz. In the experiment, two kinds of vibration signals with frequencies of 25 kHz and 15 kHz are used and the proposed interferometer SNR is 70 dB and 75 dB under the corresponding reference environment respectively. The experiment results show that the proposed interferometer can realize the measurement of large dynamic signals and has high stability. The proposed interferometer has the advantages of fast demodulation and good environmental adaptability.